Long-term follow-up of a female patient with Weber–Christian panniculitis - S. F. Akhmerov; T. Yu. Nuriakhmetova; R. Z. Abdrakipov; M. A. Afanasyeva; E. V. Sukhorukova; S. A. Lapshina; R. A. Dzamukov; D. I. Abdulganieva (Современная ревматология)
Weber–Christian disease is a rare form of lobular panniculitis characterized by painful subcutaneous nodules on the trunk and limbs commonly concurrent with systemic manifestations and a tendency to relapse. Known are only sporadic cases of a long-term (more than 5-year) followup of patients with Weber–Christian disease. For this reason, there are neither prognostic criteria for the disease no proven conventional treatment option now. The paper describes a clinical case of a female patient with a verified diagnosis of Weber–Christian disease who has a sustained subclinical remission due to low-dose prednisone use and basic antirecurrent therapy.